MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN PROBING PROMPTING PADA MATERI HIDROKARBON KELAS X DI SMA PGRI 6 BANJARMASIN - Ellis Kumala Devi; Mahdian Mahdian (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2015)
Abstract. Has done research on learning Probing prompting the hydrocarbon material class X-1 SMA PGRI 6 Banjarmasin. This study aims to determine (1) the implementation of teacher learning, (2) student activities, (3) improving student learning outcomes, (4) student response. This study used a research design class action (PTK) with 2 cycles. Each cycle consists of planning, action, observation and evaluation, as well as analysis and reflection. The subjects were students of class X-1 SMA PGRI 6 Banjarmasin the number of 26 people. The data include the observation of teacher activity, student activity and student response. Data were collected using the learning outcomes achievement test were collected using multiple choice questions each end of the cycle. The results showed that the learning model Probing prompting the teacher can increase the activity of both criteria in the first cycle and very good in the second cycle. Activity increased with the criteria students active in the first cycle became very active in the second cycle. Probing prompting learning model can improve student learning outcomes completeness of the average of 76.92% in the first cycle to 100% in the second cycle or an increase of 23.08%. Responded positively to the learning model Probing Hydrocarbon prompting on learning.Keywords. models probing prompting, learning outcomes, hydrocarbons, activity